Complement activation in immunological neurological disorders: mechanisms and therapeutic strategies - Chen, Jin Y.; Sanghani, Nirav; Palmer, Kaitlyn; Li, Yuebing; Lin, Feng; Abbatemarco, Justin R. (Frontiers in Neurology, 2025)
Recent advances in the understanding of immune-mediated neurological disorders have led to a paradigm shift toward pathophysiology-directed therapies. Central to this progress is a deeper appreciation of the complement system, a key component of innate immunity, and its role in neuroinflammation. Complement activation, while essential for host defense and tissue homeostasis, has been implicated increasingly in a spectrum of central and peripheral neurological disorders where complement dysregulation contributes to inflammation, cellular damage, and disease progression. Breakthroughs in conditions such as myasthenia gravis and aquaporin-4 IgG-positive neuromyelitis optica spectrum disorder underscore the therapeutic potential of targeting complement pathways to improve patient outcomes. In this review, we provide a comprehensive overview of complement activation pathways, regulatory controls, and their involvement in various autoimmune neurological diseases. We also highlight current and emerging complement-targeted therapies, many of which are now completing or entering clinical trials. Together, these insights offer a holistic perspective on the complement system as both a contributor to and a target for intervention in neurological diseases.